A single-phase current-source converter combined with a hybrid converter for interfacing an electric vehicle and a renewable energy source - Oliveira, Cátia Patrícia Fraga (2021)
This paper presents a single-phase current-source converter (CSC) combined with a hybrid converter on the dc-link, allowing to interface an electric vehicle (EV) and a renewable energy source (RES). Therefore, the interface with the power grid is only performed through the CSC, which also permits the operation as shunt active power filter (SAPF), allowing to compensate power quality problems related with current and low power factor in the electrical installation. The whole system is composed by two main power stages, namely, the CSC that is responsible for compensating the current harmonics and low power factor, as well as operating as a grid-tied inverter or as an active rectifier, and the hybrid converter that is responsible for interfacing the dc-link of the CSC with the converters for the EV and the RES interfaces. As demonstrated along the paper, the CSC, combined with the hybrid converter on the dc-link, allows the operation as SAPF, as well as the operation in bidirectional mode, specifically for the EV operation, and also for injecting power from the RES. In the paper, the power electronics structure is described and the principle of operation is introduced, supported by the description of the control algorithms. The validation results show the proper operation of the CSC, combined with the hybrid converter on the dc-link, for the main conditions of operation, namely exchanging power with the power grid in bidirectional mode and operating as a SAPF.